EPS Mid-Career Award 2014: The control of Attention in Visual Search: Cognitive and Neural Mechanisms. Issue 12 (December 2015) - Eimer, Martin
In visual search, observers try to find known target objects among distractors in visual scenes where the location of the targets is uncertain. This review article discusses the attentional processes that are active during search and their neural basis. Four successive phases of visual search are described. During the initial preparatory phase, a representation of the current search goal is activated. Once visual input has arrived, information about the presence of target-matching features is accumulated in parallel across the visual field (guidance). This information is then used to allocate spatial attention to particular objects (selection), before representations of selected objects are activated in visual working memory (recognition). These four phases of attentional control in visual search are characterized both at the cognitive level and at the neural implementation level. It will become clear that search is a continuous process that unfolds in real time. Selective attention in visual search is described as the gradual emergence of spatially specific and temporally sustained biases for representations of task-relevant visual objects in cortical maps.